Security and the Traumatized Street Child: How Gender Shapes International Psychiatric Aid in Cairo - Sweis, Rania Kassab (Medical anthropology quarterly, 2018)
It is ten o'clock on a sunny and unusually chilly January morning in Cairo, Egypt. Young Amir and Hassan slouch lazily in uncomfortable plastic chairs positioned next to me. We are waiting in the entryway of Dr. Mona's enormous and high‐ceilinged psychiatric clinic. The office is funded by a French‐based international organization I will refer to hereafter as Children's Charity International (CCI). This transnational organization services those deemed most vulnerable in society, especially women and children. In Egypt, their projects primarily center on the health and welfare of adfāl al shawāri’ (street children)—a category the organization and the Egyptian state define as the country's most vulnerable and at‐risk population. While CCI policy defined street children as a singular ungendered category possessing what I refer to as a “universal young humanity”—all children suffer in the same biological ways with the same effects—this article explores what I observed as a markedly gendered distribution of humanitarian psychiatric care among a small group of street children in Cairo. Specifically, I explore how, at CCI, boys were more likely to be designated as threatening or unstable child subjects and therefore in need of psychiatric or psycho–pharmaceutical intervention than girls who generally avoided this medicalized categorization. My aim is not to question the truthfulness of homeless children's suffering, but to raise new questions about what global trauma discourses and practices do for Western‐based international organizations, their workers, and the children they intend to assist.